Retraction: [A Review on Composition and Bioactivities of Essential Oils from Prominent Piper Species] - Ramin, Norazrina Md; Salleh, Wan Mohd Nuzul Hakimi Wan; Salihu, Abubakar Siddiq; Ghani, Nurunajah Ab; Abed, Salam Ahmed (Fine Chemical Engineering, 2025)
Retraction Note: Volume 6 Issue 2, FCE-8617 DOI: https://doi.org/10.37256/fce.6220258617 The genus Piper, a prominent member of the Piperaceae family, comprises over 2,000 species and is widely distributed, especially in Southeast Asia. It is well-known for several species of medicinal and economic importance, which have been utilized in their native regions for various purposes. Piper species show remarkable diversity in tropical areas worldwide, predominantly as aromatic shrubs and trees that produce substantial amounts of essential oils. These oils are highly valued for their therapeutic properties and have been used for centuries in food, pharmaceuticals, and cosmetics. Recent studies on the essential oils of Malaysian Piper species have unveiled remarkable pharmacological properties. This review seeks to comprehensively explore the medicinal applications, chemical profiles, and bioactivities of essential oils derived from prominent Piper species. The information presented was gathered through extensive searches of electronic databases, including PubMed, Scopus, and Google Scholar, as well as through library-based investigations of peer-reviewed journal articles. The focus is on the chemical components of Piper species, particularly their essential oils, offering insights into selecting species with optimal chemical profiles for various applications.